Novel anchoring group-based hole transport material and preparation method and application thereof
A hole transport material with a novel anchoring group, featuring a thiophene unit and long-chain alkyl group, improves solubility and interfacial contact, enhancing photoelectric conversion efficiency in PIN-type perovskite solar cells by addressing anchoring group limitations in existing materials.
Patent Information
- Application Number
- CN202411351433.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Current self-assembled hole transport materials in perovskite solar cells focus on the core conjugated unit but lack improvements on the anchoring group, leading to issues such as poor solubility, limited types, difficult solution preparation, and mismatched energy levels with perovskites, which hinder the growth and uniform deposition of the perovskite layer.
A hole transport material with a novel anchoring group, composed of a thiophene unit and long-chain alkyl group, forming a D1-D2-A type conjugated system, is developed, enhancing electron push-pull ability, reducing energy level differences, and improving interfacial contact with the perovskite layer through the use of phosphonic acid and cyano groups.
The novel anchoring group material achieves better photoelectric conversion efficiency in PIN-type perovskite solar cells by promoting hole extraction and uniform deposition, addressing solubility and energy level mismatch issues.
Smart Images

Figure CN119219698A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoelectric conversion, and in particular to a hole transport material based on a novel anchoring group, a preparation method and an application thereof. Background Art
[0002] Self-assembled hole transport materials with anchoring groups (acetate, borate, thiol, phosphonate, etc.) have attracted much attention and are widely used in single-cell organic solar cells (OSCs), PSCs and stacked devices. They can spontaneously and orderly anchor on the surface of indium tin oxide (ITO) substrates through dehydration condensation between the anchoring groups and the hydroxyl groups on the surface of the ITO substrate, changing the work function of ITO while enhancing the transport of interfacial charges, which greatly promotes the development of inverse perovskite solar cell devices and their stacked devices. However, these self-assembled hole transport materials currently focus on the core conjugated unit, but lack improvements on the anchoring group. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a hole transport material based on a novel anchoring group and a preparation method and application thereof, so as to solve the problem that the current self-assembled hole transport materials focus on the core conjugated unit but lack improvements on the anchoring group.
[0004] To achieve the above object, the present invention proposes a hole transport material based on a novel anchoring group, the chemical structure of the hole transport material based on the novel anchoring group is shown in Formula I: (Formula I), wherein the R group is , , , , , , At least one of the following, n is an integer, 2≤n≤6.
[0005] In order to achieve the above object, the present invention also proposes a method for preparing the above-mentioned hole transport material based on the novel anchoring group, comprising the following steps: S1: mixing compound A, 1,2-dibromobutane, tetrabutylammonium bromide and a first solvent, heating the mixture for reaction, extracting, drying and purifying by column chromatography to obtain compound B; S2: heating compound B, thiophene carboxaldehyde and palladium catalyst in a second solvent for reaction, followed by extraction, drying and column chromatography purification to obtain compound C; S3: Compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed, the mixture is heated to reflux under an inert atmosphere, and then extracted, dried and purified by column chromatography to obtain Compound D; S4: dissolving compound D in dichloromethane, adding bromotrimethylsilane under an inert atmosphere, allowing to stand, adding methanol and evaporating to obtain compound E; Among them, the structural formulas of compound A, compound B, compound C, compound D, and compound E are respectively: , , , , .
[0006] Optionally, in step S1, the ratio of compound A, 1,2-dibromobutane and tetrabutylammonium bromide is (3.5~4.5) mmol: (9.5~10) mL: (0.5~1) mmol; and / or, the ratio of compound A to the first solvent is (0.5~0.7) g: (2.0~2.5) mL.
[0007] Optionally, in step S2, the molar ratio of compound B to thiophene carboxaldehyde is 1:(1.2-1.7); and / or, the ratio of compound B to the second solvent is (50-57) mg:(15-50) mL.
[0008] Optionally, in step S3, the compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed in a ratio of (60-65) mg: (300-700) μL: (15-25) mL: (0.5-2) mL.
[0009] Optionally, in step S4, the ratio of compound D to dichloromethane, trimethylsilyl bromide, and methanol is (180-220) mg: (20-50) mL: (300-500) μL: (10-20) mL.
[0010] Optionally, the palladium catalyst comprises Pd(PPh 3 ) 4 , Pd(PPh 2 )Cl 2 , Pd(dppf)Cl 2 , Pd 2 (dba) 3 、Pd(OAc) 2 At least one of; and / or, the first solvent comprises an aqueous solution of potassium hydroxide, the mass concentration of the potassium hydroxide is 45% to 55%; and / or, the second solvent comprises anhydrous potassium carbonate, water and tetrahydrofuran.
[0011] Optionally, the volume ratio of tetrahydrofuran to water in the second solvent is 8-15:1, and the concentration of anhydrous potassium carbonate is 15 mg / ml-30 mg / ml.
[0012] To achieve the above objectives, the present invention also proposes an application of the above-mentioned hole transport material based on the novel anchoring group, wherein the hole transport material based on the novel anchoring group is the above-mentioned hole transport material, or is the hole transport material prepared by the above-mentioned preparation method, and the hole transport material based on the novel anchoring group is applied to a hole transport layer.
[0013] Optionally, the hole transport layer comprises a hole transport layer of a perovskite solar cell, and the perovskite solar cell is a PIN-type perovskite solar cell.
[0014] Optionally, the preparation of the perovskite solar cell comprises the following steps: S1: pre-treating conductive glass; S2: dripping an anhydrous ethanol solution of a hole transport material with a pipette, spin coating, and thermal annealing to remove the anhydrous ethanol to obtain a hole transport layer of the perovskite solar cell; S3: preparing a component composed of Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03 ) 3 The perovskite precursor solution is transferred and spin-coated on the hole transport layer, and then chlorobenzene is added and annealed to obtain a perovskite light-absorbing layer; S4: an electron transport layer is arranged on the perovskite light-absorbing layer; S5: an electrode is arranged on the electron transport layer.
[0015] Optionally, in the preparation of the perovskite solar cell, the concentration of the hole transport material in the anhydrous ethanol solution of the hole transport material is 0.3 mg·mL -1 ~3 mg mL -1 ; and / or, the concentration of the perovskite precursor solution is 1.5 mol·L -1 ~2 mol·L -1 .
[0016] Beneficial effects of the present invention: The present invention provides a hole transport material, which is composed of a thiophene unit containing a long-chain alkyl group and an anchoring group, forming a unique D1-D2-A type conjugated system. The chemical composition enables it to have a strong electron push-pull ability. At the same time, the introduction of thiophene also weakens the interaction between molecules, increases the steric hindrance between molecules, avoids the unfavorable accumulation of molecules, and is conducive to the solution processing of the material. At the same time, the introduction of cyano and thiophene deepens the highest occupied energy level of the molecule itself, reduces the energy level difference with perovskite, and promotes the extraction of holes. Phosphonic acid and cyano as strong electron-withdrawing groups not only further optimize the energy level structure of the material, but also improve the interface contact with the perovskite layer, which is conducive to the uniform deposition of perovskite. The hole transport material based on the novel anchoring group of the present invention is applied to PIN-type perovskite solar cells to obtain a good photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 The current density-voltage curve of the embodiment of the present invention applied to the perovskite solar cell.
[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0021] Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning in the art to which the claimed subject matter belongs, including: Jsc: short-circuit current, the current density that a solar cell can generate without external load.
[0022] Voc: Open circuit voltage, the voltage across the solar cell when no current is flowing.
[0023] FF: Fill factor, which measures the degree to which a solar cell approaches the ideal diode characteristics under working conditions, and is the ratio of efficiency to current density.
[0024] PCE: Photovoltaic conversion efficiency The efficiency of solar cells in converting light energy into electrical energy.
[0025] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0026] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0027] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0028] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0029] Self-assembled hole transport materials with anchoring groups (acetate, borate, thiol, phosphonate, etc.) have attracted much attention and are widely used in single-cell organic solar cells (OSCs), PSCs and stacked devices. They can spontaneously and orderly anchor on the surface of indium tin oxide (ITO) through dehydration condensation between the anchoring groups and the hydroxyl groups on the surface of the ITO substrate, changing the work function of ITO while enhancing the transport of interfacial charges, which greatly promotes the development of inverse perovskite solar cell devices and their stacked devices.
[0030] However, this type of HTL still has problems such as poor solubility, few available types, difficult solution preparation, and mismatch between material energy levels and various perovskites; in addition, its poor surface wettability still limits the growth of the upper perovskite, making it difficult for the perovskite to cover the substrate. On the other hand, the composition of self-assembled small molecules is divided into core conjugated units, spacer groups, and anchoring groups. At present, most of the structural innovations are on the core conjugated units, but the anchoring groups are mostly fixed on the fixed combination of fatty chain alkanes and anchoring groups, but there is a lack of improvement on the anchoring groups.
[0031] In order to solve the above problems, the present invention proposes a hole transport material based on a novel anchoring group. The chemical structure of the hole transport material based on the novel anchoring group is shown in Formula I: (Formula I), wherein the R group is , , , , , , At least one of the following, n is an integer, 2≤n≤6.
[0032] The hole transport material based on the new anchoring group is composed of a thiophene unit containing a long-chain alkyl group and an anchoring group, forming a unique D1-D2-A type conjugated system, which refers to a molecular design with an electron donor (D1), an electron acceptor (D2) and an electron donor (A). Such a structure helps to improve the photoelectric properties of the material, and the chemical composition gives it a strong electron push-pull ability.
[0033] The carbon chain will increase the steric hindrance, affecting the stacking and arrangement of the molecules, and the length of the carbon chain will affect the electron cloud distribution and degree of conjugation of the molecule, thereby changing the electronic properties of the molecule.
[0034] Thiophene is a five-membered heterocyclic compound containing a sulfur atom. The introduction of thiophene also weakens the interaction between molecules, increases the steric hindrance between molecules, improves the electron affinity and electron repulsion of the material, avoids the unfavorable stacking of molecules, and is beneficial to the solution processing of the material.
[0035] At the same time, the introduction of cyanide and thiophene deepens the highest occupied energy level of the molecule itself, reduces the energy level difference with perovskite, and promotes the extraction of holes. Phosphonic acid and cyanide, as strong electron-withdrawing groups, not only further optimize the energy level structure of the material, but also improve the interfacial contact with the perovskite layer, which helps the adhesion between the material and the perovskite layer and is conducive to the uniform deposition of perovskite.
[0036] This scheme applies hole transport materials based on new anchoring groups to PIN-type perovskite solar cells. Through sophisticated molecular design and chemical composition, good interface contact with the perovskite layer and efficient hole transport are achieved, thereby obtaining better photoelectric conversion efficiency.
[0037] In some embodiments, the value of n is 4 to 6. In some embodiments, the value of n is any value of 2, 3, 4, 5 or 6.
[0038] In order to solve the above problems, the present invention also proposes a method for preparing the hole transport material based on the novel anchoring group, comprising the following steps: S1: Compound A, 1,2-dibromobutane, tetrabutylammonium bromide and a first solvent are mixed, and the mixture is heated for reaction, extracted, dried and purified by column chromatography to obtain compound B; In some embodiments, the temperature of the temperature-raising reaction is 65° C. to 75° C. In some embodiments, after the compound A, 1,2-dibromobutane, tetrabutylammonium bromide and the first solution are mixed, the temperature of the temperature-raising reaction is any value between 65° C. and 75° C., such as 65° C., 67° C., 69° C., 71° C., 73° C., and 75° C.
[0039] In some embodiments, the solution is dried over anhydrous magnesium sulfate, spin-dried and purified using silica gel column chromatography.
[0040] S2: heating compound B, thiophene carboxaldehyde and palladium catalyst in a second solvent for reaction, followed by extraction, drying and column chromatography purification to obtain compound C; In some embodiments, the heating reaction is carried out under N 2 The mixture was washed with water and extracted with dichloromethane three times, and then the mixture was heated to 65°C to 75°C and stirred overnight at this temperature. After the solution was cooled to room temperature, the mixture was washed with water and extracted with dichloromethane three times. 2 SO 4 The crude product was dried on a rotary evaporator and purified by column chromatography (hexane / dichloromethane = 6 / 1 vol / vol) to obtain a pure product. CH 2 Cl 2 , compound C was obtained.
[0041] S3: Compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed, the mixture is heated to reflux under an inert atmosphere, and then extracted, dried and purified by column chromatography to obtain Compound D; In some embodiments, the temperature is raised to 110° C. and the reflux reaction is maintained for 10 hours. If the reflux time is insufficient, the final target product may have a lower content; and if the time is too long, the desired product may over-react or decompose.
[0042] In some embodiments, drying is spin drying.
[0043] In some embodiments, the extracting comprises extracting with dichloromethane multiple times, the multiple times being no less than three times.
[0044] In some embodiments, the residue was purified as and by column chromatography (dichloromethane:methanol=10:1) to obtain Compound D as a powder.
[0045] S4: dissolving compound D in dichloromethane, adding bromotrimethylsilane under an inert atmosphere, allowing to stand, adding methanol and evaporating to obtain compound E; In this solution, the inert atmosphere includes an atmosphere in which oxygen is removed by evacuating the atmosphere three times with nitrogen or a rare gas to avoid the occurrence of side reactions in an oxygen environment.
[0046] In this scheme, the structural formulas of compound A, compound B, compound C, compound D, and compound E are respectively: , , , , .
[0047] In this scheme, the above reaction process is: .
[0048] Furthermore, in step S1, the ratio of compound A, 1,2-dibromobutane and tetrabutylammonium bromide is (3.5~4.5) mmol: (9.5~10) mL: (0.5~1) mmol; the ratio of compound A to the first solvent is (0.5~0.7) g: (2.0~2.5) mL.
[0049] In some embodiments, the ratio of compound A, 1,2-dibromobutane and tetrabutylammonium bromide is any ratio among 3.5mmol:9.5mL:0.6mmol, 4mmol:10mL:0.5mmol, 4.5mmol:10mL:1mmol, etc. (3.5~4.5)mmol:(9.5~10)mL:(0.5~1)mmol.
[0050] In some embodiments, the ratio of compound A to the first solvent is 0.5 g / 2.0 mL, 0.5 g / 2.1 mL, 0.5 g / 2.2 mL, 0.5 g / 2.4 mL, 0.6 g / 2.0 mL, 0.6 g / 2.4 mL, 0.7 g / 2.0 mL, or any ratio between (0.5 and 0.7) g: (2.0 and 2.5) mL.
[0051] Further, in step S2, the molar ratio of compound B to thiophene carboxaldehyde is 1:(1.2-1.7); The ratio of compound B to the second solvent is (50-57) mg: (15-50) mL.
[0052] In some embodiments, the molar ratio of compound B to thiophene carboxaldehyde is any ratio between 1:1.2, 1:1.5, 1:1.7, etc. 1:(1.2-1.7).
[0053] In some embodiments, the ratio of compound B to the second solvent is any ratio of 50:20, 53:25, 57:45, etc. (50-57) mg: (15-50) mL.
[0054] Further, in step S3, the compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed in a ratio of (60-65) mg: (300-700) μL: (15-25) mL: (0.5-2) mL.
[0055] In some embodiments, the mixture ratio of compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine is 60 mg: 400 μL: 20 mL: 1 mL, 65 mg: 500 μL: 22 mL: 0.5 mL, 65 mg: 700 μL: 25 mL: 2 mL, etc., any ratio among (60-65) mg: (300-700) μL: (15-25) mL: (0.5-2) mL.
[0056] Furthermore, in step S4, the ratio of compound D to dichloromethane, trimethylsilyl bromide, and methanol is (180-220) mg: (20-50) mL: (300-500) μL: (10-20) mL.
[0057] In some embodiments, the ratio of compound D to dichloromethane, trimethylsilyl bromide, and methanol is 200 mg: 400 mL: 400 μL: 15 mL, 185 mg: 30 mL: 350 μL: 13 mL, 220 mg: 50 mL: 500 μL: 15 mL, or any ratio among (180-220) mg: (20-50) mL: (300-500) μL: (10-20) mL.
[0058] Furthermore, the palladium catalyst comprises Pd(PPh 3 ) 4 , Pd(PPh 2 )Cl 2 , Pd(dppf)Cl 2 , Pd 2 (dba) 3 、Pd(OAc) 2At least one of the following: the first solvent comprises an aqueous solution of potassium hydroxide, the mass concentration of the potassium hydroxide being 45% to 55%; the second solvent comprises anhydrous potassium carbonate, water and tetrahydrofuran.
[0059] In some embodiments, the palladium catalyst is preferably Pd(PPh 3 ) 4 .
[0060] In some embodiments, the mass concentration of potassium hydroxide is preferably 50%.
[0061] Further, the volume ratio of tetrahydrofuran to water in the second solvent is 8 to 15:1, and the concentration of anhydrous potassium carbonate is 15 mg / ml to 30 mg / ml. In some embodiments, the second solvent is anhydrous potassium carbonate (120 mg, 0.87 mmol), 2 ml of water, and 15 ml of tetrahydrofuran are added to a double-necked flask in sequence. The three are used to create a solvent system of alkaline organic mixed water, and the fixed ratio is 120 mg: 2 ml: 15 ml, which can vary. The amount of water is 2 to 5 ml, and the other components fluctuate according to the above ratio as the volume of water changes.
[0062] To solve the above problems, the present invention also proposes an application of the above-mentioned hole transport material based on the novel anchoring group, wherein the hole transport material based on the novel anchoring group is the above-mentioned hole transport material, or is the hole transport material prepared by the above-mentioned preparation method, and the hole transport material based on the novel anchoring group is applied to the hole transport layer.
[0063] Furthermore, the hole transport layer comprises a hole transport layer of a perovskite solar cell, and the perovskite solar cell is a PIN-type perovskite solar cell.
[0064] For NIP-type perovskite solar cells, the hole transport layer needs to meet different energy level position requirements and needs to adapt to the different energy level arrangements with the electron transport layer and the perovskite layer to ensure effective separation and transport of charges, especially to coordinate with the adjacent electron transport layer in chemical properties to avoid adverse interactions.
[0065] Different from NIP-type perovskite solar cells, for PIN-type perovskite solar cells, the hole transport layer needs to meet a higher hole mobility to quickly transport holes and reduce recombination losses; better energy level matching, and the energy levels of the perovskite layer and the electrode must be well matched to promote the effective extraction and transmission of holes; better stability: the chemical properties can be kept stable during the preparation and operation of the perovskite layer.
[0066] The hole transport material based on the novel anchoring group in this scheme is suitable for PIN-type perovskite solar cells.
[0067] Furthermore, the preparation of the perovskite solar cell comprises the following steps: S1: pre-treated conductive glass; The ITO conductive glass was ultrasonically cleaned with deionized water containing detergent, and then ultrasonically cleaned in deionized water, acetone, and isopropanol in sequence, and the cleaned ITO conductive glass substrate was dried with a hot air gun and placed in a UV ozone treatment machine for ozone treatment. In some embodiments, the ultrasonic treatment and ozone treatment time were 20 minutes respectively.
[0068] S2: using a pipette to drop an anhydrous ethanol solution of a hole transport material, and removing the anhydrous ethanol by spin coating and thermal annealing to obtain a hole transport layer of a perovskite solar cell; The molecule was dissolved in an ethanol solution and shaken to fully dissolve it. 50 µL of anhydrous ethanol solution of a hole transport material based on a novel anchoring group was added dropwise with a pipette. Then, the spin coating process was started at a speed of 3000 rpm for 30 s. After the spin coating was completed, it was placed on a hot stage at 100 °C for 30 min of thermal annealing to remove chlorobenzene, thereby obtaining a hole transport layer.
[0069] S3: Preparation component composition is Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03 ) 3 The perovskite precursor solution is transferred to the hole transport layer and then chlorobenzene is added dropwise and then annealed to obtain a perovskite light absorbing layer; The spin coating step includes spin coating at 1000 rpm for 10 s, then spin coating at 5000 rpm for 30 s, and adding 100 μL of chlorobenzene within 20 to 25 s after the second program is started, and then annealing the sample on a 150° C. hot stage for 10 minutes to form a perovskite light absorbing layer.
[0070] S4: Arranging an electron transport layer on the perovskite light absorbing layer; In some embodiments, the electron transport layer is a C60 layer.
[0071] S5: Arranging an electrode on the electron transport layer.
[0072] In some embodiments, the electrode material is Au or Ag.
[0073] Furthermore, in the preparation of the perovskite solar cell, the concentration of the hole transport material in the anhydrous ethanol solution of the hole transport material is 0.3 mg·mL -1 ~3 mg mL -1; The concentration of the perovskite precursor solution is 1.5 mol·L -1 ~2 mol·L -1 .
[0074] In some embodiments, the concentration of the hole transport material is 0.5 mg·mL -1 , 1mg·mL -1 , 1.5mg·mL -1 , 2mg·mL -1 , 2.5mg·mL -1 , 3mg·mL -1 Equivalent to 0.3 mg mL -1 ~3 mg mL -1 Any value in .
[0075] Embodiment 1: Synthesis of compound B: Add raw material compound 1 (0.676 g, 4.05 mmol), 1,2-dibromobutane 9.7 mL, tetrabutylammonium bromide (260.2 mg, 0.81 mmol) and 2.2 mL of 50% KOH aqueous solution in a 100 mL reaction tube. Then heat to 70 ° C and react overnight. After the spot plate reaction is complete, the reaction mixture is cooled to room temperature, washed with water, and extracted with dichloromethane. Dry with anhydrous magnesium sulfate, spin dry and purify with silica gel column chromatography (petroleum ether / dichloromethane, v / v, 8:1) to obtain compound B (0.480 g, 71%); Synthesis of compound C: Compound B (54.8 mg, 0.2 mmol), 5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)thiophene-2-carboxaldehyde (71.4 mg, 0.3 mmol), tetrakis(triphenylphosphine)palladium (18.53 mg, 0.016 mmol), anhydrous potassium carbonate (120 mg, 0.87 mmol), 2 ml of water, and 15 ml of tetrahydrofuran were added into a two-necked flask in sequence under N 2 The atmosphere was purged three times to remove oxygen, and the above solution was heated to 65°C and stirred at this temperature overnight. After the solution was cooled to room temperature, the mixture was washed with water and extracted three times with dichloromethane. 2 SO 4 The crude product was dried on a rotary evaporator and purified by column chromatography (hexane / dichloromethane = 6 / 1 vol / vol) to obtain a pure product. CH 2 Cl 2 , compound C (45.10 mg, 82.3%) was obtained; Synthesis of compound D: In a 50 ml round-bottom flask, compound C (63.88 mg, 0.2 mmol), 2-diethoxyphosphorylacetonitrile (500 μl), toluene (20 ml) and piperidine (0.5 ml) were added under nitrogen protection. The temperature was raised to 110 ° C and the reflux reaction was maintained for 10 hours. After the reactants were cooled to room temperature, the organic solvent was removed by rotary evaporation, the remaining solid was dissolved in dichloromethane, washed with water, and the organic phase was collected and dried over anhydrous sodium sulfate. Dichloromethane was removed by rotary evaporation under reduced pressure, and the residue was purified by column chromatography (dichloromethane: methanol = 10: 1) to obtain a powdered compound D (50.46 mg, 79.0%); Synthesis of Compound E: The obtained Compound D (200 mg) was dissolved in 20 mL of dichloromethane, and 400 μl of TMSbr was added under argon protection. The solution was allowed to stand overnight, and 10 ml of methanol was added. The solvent was removed by rotary evaporation under reduced pressure. Pure Compound E was obtained in the form of powder.
[0076] Embodiment 2: The preparation method is the same as that of Example 1, except that reactant 1 is 3,11-dimethoxy-7H-dibenzo[c,g]carbazole .
[0077] Embodiment 3: The preparation method is the same as that of Example 1, except that reactant 1 is 2,7-dibromo-9,9-dimethyl-9,10-dihydroacridine .
[0078] Embodiment 4: The preparation method is the same as that of Example 1, except that: the prepared hole transport material based on the novel anchoring group has n=6.
[0079] Embodiment 5: The preparation method is the same as that of Example 1, except that: the prepared hole transport material based on the novel anchoring group has n=2.
[0080] Furthermore, the above-mentioned Example 1 is used to prepare a perovskite solar cell, and the preparation steps include: 1. Cleaning of ITO conductive glass The protective film of the ITO conductive glass used in the experiment was removed, and it was first ultrasonically cleaned with deionized water containing detergent, and then ultrasonically treated in deionized water, acetone, and isopropanol for 20 min in sequence.
[0081] 2. Preparation of hole transport layer Use a hot air gun to dry the cleaned ITO conductive glass substrate and place it in a UV ozone treatment machine for 20 min. Dissolve the molecule in an ethanol solution and shake it to fully dissolve it, with a concentration of 0.3-3 mg·mL-1. Take out the ITO and wait for it to cool to room temperature, then place it on a homogenizer in a nitrogen atmosphere in a glove box, use a pipette to drop 50 µL of a uniformly dissolved 4PACz-T-CN anhydrous ethanol solution, and then start the spin coating program with a spin coating speed of 3000 rpm and a time of 30 s. After the spin coating is completed, place it on a hot stage at 100 ° C for 30 min of thermal annealing to remove the residual solvent, and the hole transport layer can be obtained.
[0082] 3. Preparation of perovskite active layer The components of the perovskite precursor solution used in the experiment are Cs0.05FA0.85MA0.1Pb(I0.97Br0.03)3, and the concentration of the precursor solution is 1.61 mol·L-1. A mixture of 19.8 mg CsI, 16.2 mg MABr, 20.3 mg MACl, 224.4 mg FAI, and 742.2 mg PbI2 powders was dissolved in 1 mL of anhydrous DMF / DMSO mixture solvent (4 / 1, v / v) and stirred at 60 °C for 2 hours to fully dissolve.
[0083] The perovskite film was prepared by a one-step method, and the anti-solvent was chlorobenzene. 50 µL of the perovskite precursor solution was transferred to the hole transport layer and spin-coated at 1000 rpm for 10 s and 5000 rpm for 30 s. 100 µL of chlorobenzene was added dropwise within 20 to 25 s after the second program was started, and the sample was then annealed on a 150°C hot plate for 10 minutes to form a perovskite active layer.
[0084] 4. Preparation of functional layer and its metal electrode layer In the glove box, the substrate after the above treatment was placed in a metal vacuum evaporation chamber, and then 35 nm thick C60, 7 nm thick BCP and 100 nm Ag electrode were sequentially evaporated at a high vacuum degree, finally obtaining a complete PSCs device with an area of 0.06 cm2.
[0085] Under standard sunlight (AM 1.5G), the device performance of the perovskite solar cell was tested. The test results are shown in the attached manual. Figure 1. As can be seen from the figure, the open circuit voltage Voc of the perovskite solar cell reverse scanning device using 4PACz-T-CN as a hole transport material is 1.131 V, the short circuit current is 24.52 mA / cm-2, the fill factor is 83.25%, and the photoelectric conversion efficiency is 23.08%. The results show that 4PACz-T-CN based on the new anchoring group can be used as a hole transport material in inverted perovskite solar cell devices. At the same time, the new anchoring group strategy has great application potential in the design and synthesis of self-assembled small molecules in perovskite solar cells.
[0086] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A hole transport material based on a novel anchoring group, characterized in that: The chemical structure of the hole transport material based on the novel anchoring group is shown in Formula I: (Formula I), Among them, the R group is , , , , , , At least one of the following, n is an integer, 2≤n≤6.
2. A method for preparing a hole transport material based on a novel anchoring group as claimed in claim 1, characterized in that: The following steps are involved: S1: Compound A, 1,2-dibromobutane, tetrabutylammonium bromide and a first solvent are mixed, and the mixture is heated for reaction, extracted, dried and purified by column chromatography to obtain compound B; S2: heating compound B, thiophene carboxaldehyde and palladium catalyst in a second solvent for reaction, followed by extraction, drying and column chromatography purification to obtain compound C; S3: Compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed, the mixture is heated to reflux under an inert atmosphere, and then extracted, dried and purified by column chromatography to obtain Compound D; S4: dissolving compound D in dichloromethane, adding bromotrimethylsilane under an inert atmosphere, allowing to stand, adding methanol and evaporating to obtain compound E; Among them, the structural formulas of compound A, compound B, compound C, compound D, and compound E are respectively: , , , , .
3. The method for preparing a hole transport material based on a novel anchoring group according to claim 2, characterized in that: In step S1, the ratio of compound A, 1,2-dibromobutane and tetrabutylammonium bromide is (3.5-4.5) mmol: (9.5-10) mL: (0.5-1) mmol; And / or, the ratio of compound A to the first solvent is (0.5-0.7) g: (2.0-2.5) mL.
4. The method for preparing a hole transport material based on a novel anchoring group according to claim 2, characterized in that: In step S2, the molar ratio of compound B to thiophene carboxaldehyde is 1:(1.2-1.7); And / or, the ratio of compound B to the second solvent is (50-57) mg: (15-50) mL.
5. The method for preparing a hole transport material based on a novel anchoring group according to claim 2, characterized in that: In step S3, compound C, 2-diethoxyphosphorylacetonitrile, toluene and piperidine are mixed in a ratio of (60-65) mg: (300-700) μL: (15-25) mL: (0.5-2) mL.
6. The method for preparing a hole transport material based on a novel anchoring group according to claim 2, characterized in that: In step S4, the ratio of compound D to dichloromethane, trimethylsilyl bromide, and methanol is (180-220) mg: (20-50) mL: (300-500) μL: (10-20) mL.
7. The method for preparing a hole transport material based on a novel anchoring group according to claim 2, characterized in that: The palladium catalyst comprises at least one of Pd(PPh3)4, Pd(PPh2)Cl2, Pd(dppf)Cl2, Pd2(dba)3, and Pd(OAc)2; And / or, the first solvent comprises an aqueous solution of potassium hydroxide, and the mass concentration of the potassium hydroxide is 45% to 55%; And / or, the second solvent comprises anhydrous potassium carbonate, water and tetrahydrofuran.
8. The method for preparing a hole transport material based on a novel anchoring group according to claim 7, characterized in that: The volume ratio of tetrahydrofuran to water in the second solvent is 8-15:1, and the concentration of anhydrous potassium carbonate is 15 mg / ml-30 mg / ml.
9. An application of a hole transport material based on a novel anchoring group, characterized in that: The hole transport material based on the novel anchoring group is the hole transport material as claimed in claim 1, or is the hole transport material prepared by the preparation method as claimed in any one of claims 2 to 8, and the hole transport material based on the novel anchoring group is applied to the hole transport layer.
10. The use of the hole transport material according to claim 9, characterized in that: The hole transport layer comprises a hole transport layer of a perovskite solar cell, and the perovskite solar cell is a PIN-type perovskite solar cell.
11. The use of the hole transport material according to claim 10, characterized in that: The preparation of the perovskite solar cell comprises the following steps: S1: pre-treated conductive glass; S2: using a pipette to drop an anhydrous ethanol solution of a hole transport material, and removing the anhydrous ethanol by spin coating and thermal annealing to obtain a hole transport layer of a perovskite solar cell; S3: Preparation component composition is Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03 )3, transfer the perovskite precursor solution to the hole transport layer, spin-coat it, drop chlorobenzene, and then anneal to obtain a perovskite light absorbing layer; S4: Arranging an electron transport layer on the perovskite light absorbing layer; S5: Arranging an electrode on the electron transport layer.
12. The use of the hole transport material according to claim 11, characterized in that: In the preparation of the perovskite solar cell, the concentration of the hole transport material in the anhydrous ethanol solution of the hole transport material is 0.3 mg·mL -1 ~3 mg mL -1 ; And / or, the concentration of the perovskite precursor solution is 1.5 mol·L -1 ~2 mol·L -1 .
Citation Information
Cited By
Dihydroacridine bridged self-assembled molecular material and preparation method therefor, and preparation method for perovskite module
WO2026170851A1
